Economics of war and peace economic, legal and political perspectives - Goldsmith, Benjamin E.; Brauer, Jurgen, 1957- (Emerald, 2010)
Economies of War and Peace: Economic, Legal, and Political Perspectives brings together recent, cutting-edge research on economic factors affecting peace and war. This important area of continuing research was the focus of an international conference held at the University of Sydney in June 2009 and these chapters are partly drawn from among the best contributions to that meeting. The book weaves together threads from a number of themes in current research including new theoretical perspectives on the economic foundations of peace, violence and war within countries, connections between international trade and inter-state conflict, and the role of legal/institutional factors in international and internal conflict. Through a focused exploration of these related topics emerge areas of scholarly consensus as well as areas of continued debate. International in scope, it is the only book to explicitly bring together economic, legal and political scholarship to focus on the problem of conflict. It employs a range of modern social science analytical methods, including qualitative cases, econometrics, and game-theoretic models, to rigorously advance understanding of conflict within and between countries.
Description based on print version record.
Keywords: War -- Economic aspects.; Peace -- Economic aspects.; Political violence -- Economic aspects.; War (International law); Politics and war.; International relations.; Political economy.; Political Science -- Economic Conditions.; Political Science -- Political Freedom & Security -- International Security.; elektronické knihy; electronic books